Pancasila as a Margin of Appreciation in the Implementation of Human Rights in Indonesia Citizenship Education Perspective - Isnin, Harum; Wardhani, Novia Wahyu (Jurnal Scientia Indonesia, 2021)
Pancasila has become a philosophy, ideology, and way of life for the Indonesian people in the life of the nation and state. The entire implementation and implementation of the state, especially the implementation of human rights in Indonesia, has implications for the values in Pancasila. There are still many cases of gross human rights violations and minor human rights violations that occur in Indonesia. There needs to be an appreciation and respect for human rights owned by the Indonesian people to be recognized with good appreciation in their implementation. This paper is an analysis of the appreciation, respect, and limitations regarding the extent to which human rights are implemented in Indonesia. By using the literature review method which results in an analysis that Pancasila is the margin of appreciation in the implementation of human rights in Indonesia with the implications of human rights that are adapted to socio-cultural conditions and the philosophy of life view of the Indonesian people to continue to strive to ensure respect for individual rights with national interests.